2011
DOI: 10.1074/jbc.m110.150177
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Architecture of Leukotriene C4 Synthase with Two Arginine Residues

Abstract: Leukotriene (LT) C4 and its metabolites, LTD4 and LTE4, are involved in the pathobiology of bronchial asthma. LTC4 synthase is the nuclear membrane-embedded enzyme responsible for LTC4 biosynthesis, catalyzing the conjugation of two substrates that have considerably different water solubility; that amphipathic LTA4 as a derivative of arachidonic acid and a water-soluble glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 57 publications
2
31
0
2
Order By: Relevance
“…The estimated K m for GSH and LTA 4 -Me were 0.27 AE 0.05 mM and 5.0 AE 0.3 mM, respectively. These K m values are comparable with those in our previous report (19).…”
Section: Analysis Of Inhibition Kineticssupporting
confidence: 92%
See 3 more Smart Citations
“…The estimated K m for GSH and LTA 4 -Me were 0.27 AE 0.05 mM and 5.0 AE 0.3 mM, respectively. These K m values are comparable with those in our previous report (19).…”
Section: Analysis Of Inhibition Kineticssupporting
confidence: 92%
“…This reversible suppression shows that the compounds do not impose denaturation or aggregation of the homotrimer of LTC 4 S. However, there may be some structural changes that are implied by the compounddependent Hill slope variation. The crystal structure of the homo-trimer of LTC 4 S bound GSH showed that LTC 4 S forms three equivalent active sites between interfaces of homo-trimer (17,19). The binding of GSH as the natural substrate stabilizes the homo-trimer of LTC 4 S (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The important roles of Arg-31 and Arg-104 were recently experimentally verified. 315,316 In marked contrast, the cleft between TM1 and TM4 of adjacent monomers was not recognizable in the structure of mPGES-1. 309 Thus, the most likely entry point for PGH 2 reaching the glutathione was blocked and no alternative paths were found.…”
Section: Prostaglandin E Synthases (Pgess)mentioning
confidence: 90%